Variants of life trajectories among persons with disabilities in the context of subjective well-being and life quality - Svetlana Khazova; Inna Tikhonova; Tatiana Adeeva (Social Welfare: Interdisciplinary Approach)
The article presents the results of the study of life trajectory variants among persons with disabilities as well as their social and personal characteristics: life satisfaction, life quality assessment, well-being, and coping strategies. The total sample was 87 people. The study suggests 3 variants of life trajectories among persons with disabilities. They differ in such parameters as dynamics, narrative, connection between events and one’s emotions, modality of emotions, number of important events, and their content. The reported life quality assessments slightly characterize the life trajectory variants. We identified the difference both between the levels of one’s social well-being satisfaction and subjective well-being in the 3 variants of life trajectories. We also observe specificities of the coping strategies. The results can be used to design programs of psychological assistance, accompany persons with disabilities, develop positive life strategies, and achieve high subjective well-being levels